PEMANFAATAN BERBAGAI MACAM BIOAKTIVATOR TERHADAP EFEKTIFITAS PENGOMPOSAN DAUN JATI (Tectona grandis, L) DAN PENGARUHNYA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PUTIH (Brassica sinensis, L) - Anton Nugroho (Agro 15 UMY 071, 2015)
*71 The research titled "The Utilization of various of Bio-activator on Teak Leaves Composting and It’s Influence on Growth and Yield of White Caisim" was conducted at Klaten regency to composting proses and Gunung kidul regency to application of compos to white caisim from 15 Mart up to 15 Juny 2015. The research aims to determine the effect of various kinds of bio-activator on teak leaves composting and its influence on growth and yield of white caisim. The research was done in experimental method used 5 kinds of compost : Composting leaves of teak with a bio-activator cow rumen (A), Composting leaves of teak with a bio-activator buffalo rumen (B), Composting leaves of teak with a bio-activator goat rumen (C), Composting leaves of teak with the activator EM4 (D), and Composting leaves of teak without bio-activator (E). The research was arranged in completely randomized design with 10 treatments. The treatments are : P1= 5 tons/hectare of compost A; P2= 10 tons/hectare of compost A; P3= 5 tons/hectare of compost B; P4= 10 tons/hectare of compost B; P5= 5 tons/hectare of compost C; P6= 10 tons/hectare of compost C; P7= 5 tons/hectare of compost D; P8= 10 tons/hectare of compost D; P9= 5 tons/hectare of compost E; P10= 10 tons/hectare of compost E. The results showed that the use of bio-activator of buffalo rumen gave the better effect on the quality of teak leaves composting, and all of treatments have no significantly different to growth and yield of white caisim